Factors Associated With an Abnormal Blood Pressure Response During Exercise After Coarctation Repair. Issue 1 (January 2022) - Pivirotto, Mia; Swartz, Michael F.; McGreevy, Megan B.; Atallah-Yunes, Nader; Cholette, Jill M.; Lipshultz, Steven E.; Alfieris, George M.
Background: Although resting blood pressures following aortic arch repair or the extended end-to-end anastomosis (EEA) repair for coarctation can be physiologic, factors associated with an abnormal blood pressure response after exercise are unknown. We measured blood pressure gradients following exercise in children who had undergone previous repair in accordance with a surgical selection algorithm and sought to identify factors associated with an abnormal blood pressure response. Methods: In accordance with our practice's surgical algorithm for repair of coarctation, infants were stratified to aortic arch repair when the distal transverse arch-to-left carotid artery ratio (DTA:LCA) ≤ 1.0, or when a brachiocephalic trunk or intra-cardiac lesion requiring repair was present. A thoracotomy and EEA were otherwise used. A follow-up exercise stress test (EST) measured the arm:leg blood pressure gradient after exercise, and a gradient ≥ 20 mm Hg was defined as an abnormal blood pressure response. Results: Thirty-seven infants who had previously undergone coarctation repair (aortic arch repair-19, EEA-18) completed an EST at 12.3 ± 2.2 years of age. Thirteen (35%) children (aortic arch repair-5, EEA-8; p = .3) exhibited an abnormal blood pressure response. Factors associated with an abnormal blood pressure response included: smaller DTA:LCA ratios prior to repair (1.0 ± .2 vs. 1.2 ± .3; p = .04) and greater body weight at the time of EST (57.5 ± 19.1 vs. 40.9 ± 15.6 kg; p = .03). Conclusion: An abnormal blood pressure response following exercise is associated with smaller DTA:LCA ratios at the time of repair and increased weight during follow-up suggesting that patients with these factors warrant close observation.